Religious activity of population as factor of manifestation of social troubles associated with health and safetyn as factor of manifestation of social troubles associated with health and safety - Yavorska, Victoria; Kostaschuk, Ivan (Journal of Education, Health and Sport, 2018)
This article studies the impact peculiarities of the population’s religious activity on the manifestation of social troubles. The territory of Ukraine was chosen for research. It has been established that the religious activity of the population correlates significantly with diseases associated with moral qualities of the population, namely HIV and AIDS, tuberculosis, etc., as well as various manifestations of crimes. To establish the relationships and their justification, a method of linear correlation was chosen which helped to establish different degrees of mutual impact. The most noticeable impacts on demographic components are presented in the article.